Young Adults' Investment Decisions in Surabaya: The Influence of Financial Literacy and Risk Perception - Pavita Kelviani Chandra; Laura Brigita Pangkey; Tessa Vanina Soetanto (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2023)
Important investment decisions allocate an investor's assets in light of further consideration. As youthful investors have dominated the investor population in recent years, investors should be cautious of the elements that influence investment decisions. Despite its significance, few or no studies have examined the influence of financial literacy and risk perception on investment decisions among young adults in Surabaya. This study seeks to determine the impact of financial literacy and perception of risk in investment decision-making, specifically young adults in Surabaya, both simultaneously and individually. By distributing questionnaires to a total of 89 respondents, a basic random sampling method was utilized. Then, IBM SPSS Statistics is used to conduct a multiple Linear regression analysis on the data. The findings demonstrated that financial literacy and risk perception have a significant positive relationship with the investment decisions of young adults in Surabaya, both concurrently and separately. In addition, this research enables young adults in Surabaya to comprehend their investment decision, allowing them to comprehend the factors that influence it and obtain useful benefit.